(3GdJfXje GdbGfhfi ddTQcGJ eJYOOI GdLfSjGJ (B: s (3OQGSI bGfhfjI ebGQfI (B/ s - (3Ydi Hf SGde Hf Ydi GdHGOi s; (3gGfi SQi GdOjf (B: s ((3GdbGgQI (B: s (3Ydi Hf SGde Hf Ydi GdHGOi (B: s, 2014)
(3NdUJ GdQSGdI Gdi Cf GdTQcGJ eJYOOI GdLfSjGJ JYO ef GcKQ GdCfeGW JYHjQG Yf YhdeI GdGbJUGO fXQG deG Jedcg ef EecGfGJ eGOjI hHTQjI gGFdI JeJO Edi eNJda Ohd GdYGde h gi JeKd bhI CSGSjI ai GdGbJUGO GdYGdei ai YGdefG GdeYGUQI XgQ eUWdM GdTQcGJ eJYOOI GdLfSjGJ ai GdbQf GdKGef YTQ JbQjHG EdG Cf Jdc GdefTCJ de JJNP eSei ehMO NGUI dOi GdGbJUGOjjf h GdbGfhfjjf GdPjf GNJdahG ai hLgGJ GdfXQ HTCf gPg GdefTCJ GSJNOeJ GdQSGdI GdCSGdjH GdYdejI GdbGfhfjI dOQGSI GdTQcGJ eJYOOI GdLfSjGJ h eYQaI NUGFUgG h Cge GdeTcdGJ GdbGfhfjI GdJi jecf Cf JTcd YGFbG CeGe GdTQcGJ eJYOOI GdLfSjGJ ddGSJKeGQ ai GdOhd GdeVjaI hJfGhdJ GdJWHjb ai GdaJQI (B1990- 2014(3e cOQGSI bGfhfjI ebGQfI Hjf SdWfI YeGf h eUQs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQis
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJfXje GdbGfhfi s; (3GdTQcGJ eJYOOI GdLfSjGJ s; (3GdbGfhf GdJLGQis